Bentuk, Makna, dan Fungsi Budaya Tutur Betore di Kabupaten Paser: Forms, Meanings, and Functions of the Betore Speech Culture in Paser Regency - Rijal, Syamsul; A., Sainal; Nasrullah, Nasrullah (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2023)
Betore is one of the oral traditions in Paser Regency, East Kalimantan. This cultural practice is on the brink of extinction as only a few elderly individuals are capable of performing it. Originally used by the Paser community, specifically by young people, Betore served as a means of communication during rice harvesting in the fields and also provided entertainment amidst the fields. The process of Betore involves a responsive exchange of speech with specific themes. The resulting utterances in Betore emerge spontaneously following the evolving theme, making it an anonymous form of expression. Betore and rice harvesting are inseparable, and as a consequence, this oral tradition is increasingly eroded due to the dwindling dry agricultural land in Paser Regency. Betore can be categorized as an ancient poem since it embodies the form, meaning, and function of traditional literature. Betore follows an a-b-a and a-b-c rhyme scheme. This rhyme structure is somewhat distinct from other ancient poems in the Indonesian archipelago, although Betore appears to be more similar to talibun. The functions of Betore encompass recreational, didactic, aesthetic, moral, and religious aspects. Regarding meaning, Betore conveys advice, satire, and religious messages. Betore implicitly holds social values, promoting fraternity, unity, and togetherness.